MENINGKATKAN HASIL BELAJAR SISWA DALAM PEMBELAJARAN ILMU PENGETAHUAN SOSIAL DENGAN MENGGUNAKAN MODEL INTERAKTIF - Bari, Lela (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2013)
Based to observation of SDN 12 Child Irrigate Dadok that less atmosphere creation learn pleasant, study still have the character of conventionally of method weared [by] teacher in study of monoton. To overcome model interaktif, this research use approach qualitative and kuatitatif. Research procedure executed [by] four phase : Planning, execution, and perception of refleksi. From result of perception of cycle of I aspect learn 75%, cycle of II 96%. Student cycle aspect of I 75%, cycle of II 86%, presentase result of learning cycle student of I 65,77%, cycle of II 79,7%.   Kata Kunci : hasil belajar, pembelajaran IPS, model interaktif